2009
DOI: 10.1175/2008jamc1963.1
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Covariance Analysis of Typhoon Surface Wind and Rainfall Relationships in Taiwan

Abstract: The multivariate relationships between hourly surface wind and rainfall observations during typhoons affecting Taiwan have been investigated with maximum covariance analysis (MCA). Historical surface observations from 1987 to 2004 are used when typhoon centers were located inside the domain of 198-288N, 1178-1278E. The three leading MCA modes explain 70%, 20.6%, and 7.6% of the squared covariance fraction, and the correlation coefficients are 0.59, 0.48, and 0.49, respectively. The wind directions of the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Typhoons reduce the temperature and humidity in Southern Taiwan because of adiabatic warming (or foehn wind) on crossing the Central Mountain Range in Taiwan [ 52 ]. This phenomenon was strong during Typhoon Morakot [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typhoons reduce the temperature and humidity in Southern Taiwan because of adiabatic warming (or foehn wind) on crossing the Central Mountain Range in Taiwan [ 52 ]. This phenomenon was strong during Typhoon Morakot [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Climate change strongly affects the uplifted coral reef remnant ecosystem of the Hengchun Peninsula. The aboveground vegetation was withered by Typhoon Morakot, and the posttyphoon days were severely dry and witnessed warm foehn-like winds [ 52 ], which reduced the humidity. Plants living in such harsh, uncertain environments have been selected for their ability to survive withering typhoons; however, because of global climate change, extreme events, such as strong typhoons and droughts, occurred increasingly and more powerfully [ 15 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In nature the rainfall recharge is usually nonuniformly distributed, so temporal variation of it was considered. Referring to the works of Wartalska et al [25] and Shih [19], six recharge patterns over time shown in Figure 10 were introduced to discuss their effects on hillslope storage. Assuming the same aquifer and groundwater conditions and setting D = 5 m, θ = 5%, and γ = 0 for the simulated scenarios, Figure 11 shows the temporal variation of the water level at various durations under six recharge patterns for convergent hillslope.…”
Section: Effect Of Variable Recharge Ratesmentioning
confidence: 99%
“…These researchers have revealed that when typhoons approach Taiwan from the east before passing through the CMR, their routes are more easily estimated, and early warnings can be provided for precaution against the corresponding wind and rain. By contrast, after typhoons pass through the CMR, the routes, arrival times of wind and rain, and delays in rainfall become unpredictable [14,15]. Therefore, efficiently estimating typhoon rainfall is crucial for Taiwan.…”
Section: Introductionmentioning
confidence: 99%